Reforestation and sylvopastoral systems in Sahelian drylands: evaluating return on investment from provisioning ecosystem services, Senegal - Cesaro, Jean-Daniel; Mbaye, Tamsir; Ba, Baba; Ba, Marieme Fall; Delaye, Etienne; Akodewou, Amah; Taugourdeau, Simon (Frontiers in Environmental Science, 2023)
Since the 1960s, periodic droughts have caused severe degradation to Sahelian ecosystems, particularly in terms of reduced tree cover. Nevertheless, the rural Sahelian population continues to depend on these natural resources for pastoral livestock farming, which is their primary source of livelihood. In a context of increasing conflict, the Sahelian states and international coalitions are focusing their efforts on restoring degraded land through reforestation programs. These operations are aimed at increasing ecosystem services to generate new income for the population while ensuring the preservation of biodiversity. Through a quantification of the economic potential of the provisioning Ecosystem Services by these programs in Senegal, this paper shows that the economic viability of their operations, analyzed from the perspective of investment profitability, is questionable. It seems that local economic actors, particularly pastoralists and vulnerable communities, need to be better integrated into the planning of operations for the restoration of degraded lands in the Sahel.